Legal Protection For The Winner Of Execution Auction Over The Auction Object That Sued Before District Court - Dwi Ayu Rachmawati; Nurini Aprilianda; Siti Noer Endah (Faculty of Law, University of Mataram, 2018)
In the process of auction execution often arise a lawsuit over the auction implementation, this is because the auction of execution is done not on the willingness of the owner of the goods themselves but because the law gives authority to the creditors to conduct public auction on the guarantee of debtors that default. So in the process of conveyance of auction object from the seller to the auction buyer often cause a problem, such as can not be mastered by auction winner the auction object. The purpose of this research is to know how to find out how the legal protection for the winner of the auction of execution of mortgage rights in mastering the auction object on the auction object which filed the lawsuit to the state court. This research is done by normative method. Based on the research that has been done, the winner of the auction can not be directly mastering the auction object because there is a civil suit over the auction object are expanding following. This is as article 3 paragraph (1), (2), and subsection (3) of the regulation of the Minister of Agrarian Affairs and Spatial/head of the national land Agency number 13 Year 2017 on The Block and confiscation who explains that if there is a dispute or conflict over land rights law the land that became the object of the auction then blocking would have done. And the protection of the law against the winner of the auction provided by regulation of the Minister of finance Number 27/PMK. 06/2016 Hints would about implementation of auctions, HIR. In addition, in article 19 paragraph (1) of law No. 8 Year 1999 on the protection of Consumers and in the jurisprudence of the Supreme Court's verdict against RI No. 1068 K/Pdt/2008 Dated January 21, 2009 in National Conference MA Year 2011.